Overexpression of TRIM24 correlates with tumor progression in non-small cell lung cancer. - Haiying Li; Liangliang Sun; Zhongping Tang; Lin Fu; Ying Xu; Zixuan Li; Wenting Luo; Xueshan Qiu; Enhua Wang (PLoS ONE, 2012)
The objective of the current study was to investigate the expression pattern and clinicopathological significance of TRIM24 in patients with non-small cell lung cancer (NSCLC). The expression profile of TRIM24 in NSCLC tissues and adjacent noncancerous lung tissues was detected by immunohistochemistry. TRIM24 was found to be overexpressed in 81 of 113 (71.7%) human lung cancer samples and correlated with p-TNM stage (p = 0.0006), poor differentiation (p = 0.004), Ki67 index (p<0.0001), cyclin D1(p = 0.0096) and p-Rb expression (p = 0.0318). In addition, depleting TRIM24 expression by small interfering RNA inhibited growth and invasion in lung cell lines. Moreover, TRIM24 depletion induced cell cycle arrest at the G1/S boundary and induced apoptosis. Western blotting analysis revealed that knockdown of TRIM24 decreased the protein levels of Cyclin A, Cyclin B, Cyclin D1, cyclin E and p-Rb and increased P27 expression. These results indicate that TRIM24 plays an important role in NSCLC progression.